Improving Phosphate Efficiency by Phosphate Solubilizing Bacteria and Organic Matter Estimated by Radio Isotop (32P) Technique in Some Soils - Arie Mudjiharjati; Tri Candra Setiawati; Martinus Harsanto Pandutama (UNIVERSITY OF LAMPUNG, 2012)
Phosphorous (P) contents in many soils are varies highly along with their ability to provide available P to plant growth. Soils may contain very high in total P, but low in available P due to high P adsorbed by soil matrix and all their adsorbing agents. This research which using natural materials was aimed to increase P availability in some high-P absorption soils. The natural materials utilized for extracting P were organic matter, P extracting bacterial, and rock phosphate. Those materials were interacted to high P absorption soils which were: Oxisol, Inceptisol, and Andisol. The detail objectives of this research were: (1) to study the potential of P-extracting agents (organic matter, and P-extracting bacteria) in releasing P of three high P- absorption soils; (2) to quantify the -age of P coming from the treatments; (3) to calculate the efficiency of P utilization by plant; and (4) to quantify Residual P in soils. The P mobility was analyzed by radioisotope technique using KH232PO4 carrier free solution. The results showed that adding soil organic matter increased the available P by 15.24% in Oxisol, 40.18 in Inceptisol, and by 7.34% in Andisol. Plant sorption toward P from % P used efficiency(%-PUE) up to 60 days was still very low, 0.65 to 9.34%. This was in accordance with the residual P in soils which were still quite high ranging from 94% to 96% in Andisol, 91%97% in Inceptisol, and 96%-98% in Oxisol. The implication of the results of this research, however, is that the application of natural materials in improving soil P availability provides a longtimeresidual effect which could give benefit to the following crops.Keywords: Andisols; Inceptisol; Oxisols; P. diminuta; PUE; rock phosphate[How to Cite: Mudjiharjati A, TC Setiawati and MH Pandutama. 2012. Improving Phosphate Efficiency by Phosphate Solubilizing Bacteria and Organic Matter Estimated by Radio Isotop (32P) Technique in Some Soils. J Trop Soils, 17 (3) : 245-252. doi: 10.5400/jts.2012.17.3.245][Permalink/DOI: www.dx.doi.org/10.5400/jts.2012.17.3.245]